Steroid hormone 20‐hydroxyecdysone disturbs fat body lipid metabolism and negatively regulates gluconeogenesis in Hyphantria cunea larvae - Zhang, Sheng‐Yu; Gao, Han; Askar, Ankarjan; Li, Xing‐Peng; Zhang, Guo‐Cai; Jing, Tian‐Zhong; Zou, Hang; Guan, Hao; Zhao, Yun‐He; Zou, Chuan‐Shan (Insect science, 2023)
The steroid hormone 20‐hydroxyecdysone (20E) has been described to regulate fat body lipid metabolism in insects, but its accurate regulatory mechanism, especially the crosstalk between 20E‐induced lipid metabolism and gluconeogenesis remains largely unclear. Here, we specially investigated the effect of 20E on lipid metabolism and gluconeogenesis in the fat body of Hyphantria cunea larvae, a notorious pest in forestry. Lipidomics analysis showed that a total of 1 907 lipid species were identified in the fat body of H. cunea larvae assigned to 6 groups and 48 lipid classes. The differentially abundant lipids analysis showed a significant difference between 20E‐treated and control samples, indicating that 20E caused a remarkable alteration of lipidomics profiles in the fat body of H. cunea larvae. Further studies demonstrated that 20E accelerated fatty acid β‐oxidation, inhibited lipid synthesis, and promoted lipolysis. Meanwhile, the activities of pyruvate carboxylase, phosphoenolpyruvate carboxykinase, fructose‐1,6‐bisphosphatase, and glucose‐6‐phosphatase were dramatically suppressed by 20E in the fat body of H. cunea larvae. As well, the transcriptions of genes encoding these 4 rate‐limiting gluconeogenic enzymes were significantly downregulated in the fat body of H. cunea larvae after treatment with 20E. Taken together, our results revealed that 20E disturbed fat body lipid homeostasis, accelerated fatty acid β‐oxidation and promoted lipolysis, but negatively regulated gluconeogenesis in H. cunea larvae. The findings might provide a new insight into hormonal regulation of glucose and lipid metabolism in insect fat body. The steroid hormone 20‐hydroxyecdysone (20E) promotes lipid metabolism but inhibits gluconeogenesis in the fat body of Hyphantria cunea larvae. The effect of 20E on lipid metabolism in larval fat body of H. cunea is shown on the left: 20E increases the expression of lipase and promotes the degradation of triglycerides; 20E increases the concentrations of key enzymes (ECH and 3HCD) in fatty acid β‐oxidation pathway and the β‐oxidation intermediate (NADH); 20E upregulates the expressions of CPT1/2 and accelerates the transfer of acyl‐CoA; 20E downregulates FAS and inhibits the synthesis of fatty acids. The effect of 20E on gluconeogenesis in larval fat body of H. cunea is shown on the right: 20E suppresses the activities of 4 rate‐limiting gluconeogenic enzymes (PCase, PEPCK, FBP, G6Pase), and decreases the intermediate products (OA and PEP) in the gluconeogenesis pathway.